The effect of stress on the acute neurotoxicity of the organophosphate insecticide chlorpyrifos - Hancock, Sandra; Ehrich, Marion; Hinckley, Jonathan; Pung, Thitiya; Jortner, Bernard S. (Toxicology and applied pharmacology, 2007)
A study was conducted to determine if multiple exposures to several stress paradigms might affect the anticholinesterase effect of subsequently administered organophosphate insecticide chlorpyrifos. Male Sprague–Dawley rats were subject to daily periods of restraint, swimming, a combination of the two, or neither of the two (controls) ( n = 8/group) for 5 days per week over a six-week period. The most profound stress, as measured by reduced body weight gain and elevated levels of plasma corticosterone, was swimming. On day 39 of the study, shortly after the daily stress episode, one half of the rats in each group was dosed with 60 mg/kg chlorpyrifos subcutaneously. This had no effect on subsequent levels of plasma corticosterone. There were no stress-related differences in the degree of chlorpyrifos-induced inhibition of brain acetylcholinesterase in animals sacrificed on day 43.